Separate effects of irradiation and of graft-versus-host reaction on rat mucosal mast cells. Issue 3 (March 1989) - Cummins, A G; Munro, G H; Huntley, J F; Miller, H R; Ferguson, A
Abstract : T cell mediated immune responses in the gut can produce enteropathy and malabsorption. We have investigated the relevance of mucosal mast cells (MMC) to the mechanisms of this enteropathy by using graft-versus-host reaction (GvHR) in the rat as a model of mucosal delayed type hypersensitivity. Measurements of mucosal architecture, intraepithelial lymphocytes (IEL) and MMC counts were performed in control and experimental rats, and release of rat mast cell protease II (RMCPII) into the bloodstream was used as an index of MMC activation. In unirradiated rats, jejunal MMC count was increased on day 14 of the GvHR (mean 272/mm2 v 182 in controls, p less than 0.01), as was serum RMCPII (p less than 0.01). Irradiated rats (4.5 Gy, reconstituted with isogeneic spleen cells) had low counts of IEL and crypt hyperplasia seven to 14 days after irradiation. Irradiated rats with GvHR (induced by ip injection of parental strain spleen cells) and studied on days 7, 10 and 14, had significant enteropathy with longer crypts and higher CCPR than matched irradiated animals (p less than 0.05 on day 14 when compared with irradiation alone). Intraepithelial lymphocytes counts, however, reflected only the effect of radiation. Irradiation, with or without GvHR, led to the virtual disappearance of jejunal MMC, undetectable jejunal RMCPII and very low levels of RMCPII in serum (all p less than 0.01 when compared with unirradiated controls). These experiments show that there is a modest expansion in jejunal MMC in unirradiated rats with semiallogeneic GvHR, whereas irradiation, alone or associated with GvHR, profoundly depletes MMC for at least two weeks. The enteropathy of GvHR can evolve in the virtual absence of MMC.